Bid-ask spreads in the interbank foreign exchange markets - Bessembinder, Hendrik (Journal of Financial Economics, 1994)
This study provides evidence on quotations and bid-ask spreads in the wholesale foreign exchange market, and introduces a method to document variation in the placement of quotes relative to asset value. I find that spreads widen with proxies for inventory-carrying costs, including forecasts of price risk and a measure of liquidity costs. Increases in spreads before nontrading periods can also be attributed to inventory costs. The location of currency quotes in relation to value is not constant, and the outcome of hypothesis tests regarding changes in currency value can be sensitive to allowances for variation in quote location.